O acento do português do Brasil: controvérsias e perspectivas - Rosane Miranda Rodrigues dos Reis (2006)
The objective of this dissertation is analyse, in Metrical Phonology perspective, the several interpretations to occurrence of the primary accent in Brazil Portuguese (BP). It is separated amongst three principal groups: the chapter two shows the subjacent theories to every one offour analyses enumerated in the chapter three, where the studies have already developed by Bisol (1992), Massini-Cagliari (1995 and 1999), Pereira (1999) and Lee (1995) are introduced. The intention is compare advantage and disadvantage amongst different metrical approaches and different positions to formulation of Brazil Portugueses accent rule, it issignalizing the principal contributions and vacuum have left by each and all, appraising the phonologic value of the silabic weight in this language and its prominence or no proeminence about accent attribution. As of the vision every one detailed theories, we have in the chapter four the assumption of rhythmical and morphological factories to the explanation of the accent in this language, and the introducing of a proposal is based on interaction of these factories to describe the accentuation phenomenon of the BP.